2007
DOI: 10.1021/bi700579z
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations in Factor XIII Resulting from Activation and Inhibition Examined by Solution Based Methods and Detected by MALDI-TOF MS

Abstract: Factor XIII can be activated proteolytically by thrombin cleavage of the activation peptide or non-proteolytically by exposure to 50 mM Ca2+. The resultant transglutaminase cross-links Q and K residues within the noncovalently associated fibrin clot. Hydrogen deuterium exchange coupled with MALDI-TOF MS demonstrated that FXIII activation protects regions within the beta sandwich (98-104) and the beta barrel 1 (526-546) from deuterium, while exposing the potential Q substrate recognition site (220-230) to deute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
49
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 54 publications
6
49
0
Order By: Relevance
“…The low-affinity interaction was dependent on calcium, which induces a conformational change in the ␤-barrel 1 and the ␤-sandwich domains of thrombin-cleaved FXIII-A. [13][14][15] In addition, calcium could mediate the interaction with Glu396. However, the lowaffinity interaction was independent of catalytic activity, showing that it did not arise from a transient covalent intermediate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low-affinity interaction was dependent on calcium, which induces a conformational change in the ␤-barrel 1 and the ␤-sandwich domains of thrombin-cleaved FXIII-A. [13][14][15] In addition, calcium could mediate the interaction with Glu396. However, the lowaffinity interaction was independent of catalytic activity, showing that it did not arise from a transient covalent intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was observed that the ␣C region 233-425 does not bind to rFXIII-A activated with thrombin only but also required the presence of calcium that induces a conformational change that exposes portions of FXIII-A that are not structurally exposed in the nonactivated form [13][14][15] ( Figure 5B). Binding did not depend on catalytic activity because blocking the rFXIII-A active site Cys314 with iodoacetamide did not inhibit binding to the ␣C region 233-425, which occurred to the same degree as activated rFXIII-A in the absence of iodoacetamide ( Figure 5C).…”
Section: Nonactivated Rfxiii-a Does Not Bind Fibrinogen ␣C Region 233mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to probing FXIIIa inhibition, new insight has also been obtained regarding the conformational features associated with the activation of FXIIIa by Ca 2+ and by IIa, thus augmenting our previous investigations (174,175). The current studies thus provide valuable information about events occurring to the β sandwich, the activation peptide, the dimer interface, the catalytic core, and β barrels 1 and 2 (178). (269).…”
mentioning
confidence: 59%
“…FXIIIa has now been developed that incorporates the Q isostere 6-diazo-5-oxo-norleucine into the FXIIIa substrate peptide K9. The focus of the work has proceeded to observe in solution the conformational changes associated with inhibition by K9 DON compared to IAA (178). In addition to probing FXIIIa inhibition, new insight has also been obtained regarding the conformational features associated with the activation of FXIIIa by Ca 2+ and by IIa, thus augmenting our previous investigations (174,175).…”
mentioning
confidence: 99%